Pengaruh Klausula Fair And Equitable Treatment Pada Perjanjian Investasi Bilateral Sebagai Upaya Perlindungan Investasi Bagi Penanam Modal Asing - Putra, Dandi Riskia (Journal of Economic and Business Law Review, 2023)
To protect and encourage foreign investment, bilateral investment treaties (BITs) are often an important tool. The focus of this research is the Fair and Equitable Treatment (FET) clause, which is one of the most debated and controversial BIT clauses. This study investigates how these clauses function as protective mechanisms for foreign investors in bilateral investment agreements. This study shows that the FET clause protects investors in many ways, such as regulatory stability, legal certainty and non-discriminatory treatment. However, the way these clauses are used and interpreted varies widely, and often leaves considerable latitude for arbitrators to judge, which can sometimes impact the host country's freedom of public policy. According to this research, the text should be further clarified and FET clauses should be implemented to balance the need for investor protection with the public interest.